Development of a new method to estimate thermal performance of multilayer radiant floor. (January 2021) - Li, Qingqing; Zhang, Ye; Guo, Tieming; Fan, Jianhua
Abstract: . For a pipe-embedded concrete radiant floor, its thermal performance is essential to maintain the desired cooling/heating capacity and indoor thermal comfort. A good temperature distribution of the floor surface is very important in order to prevent occupant discomfort and avoid possible condensation in the case of floor cooling. In this study, a heat transfer model of a three-layer floor was developed by coupling 2-D and 1-D heat transfer problems. The analytical solution was developed and validated. The results of the calculations are in a good agreement with the experiments. The absolute error between the calculated and the measured floor surface temperatures was within 0.4℃. The maximum relative error was within 2.2%. The proposed method can be utilized to calculate the thermal performance of a floor, either a one-layer floor, a two-layer floor or a three-layer floor. The thermal resistance of the floor with different structures can be calculated and used to estimate thermal performance of the floor. For the typical radiant floor, the range of thermal resistance is approximately 0.15-0.45 m 2 K/W with a pipe spacing from 0.1 to 0.5 m. With the overall floor temperature obtained, it is possible to identify the percentage of the floor area with a temperature higher than the limit and to estimate the overall and local occupant comfort. Based on the thermal resistance of the floor, an ε-NTU method will be developed in the future study for design of a radiant floor. Highlights: A hybrid model of 3-D heat transfer problem of radiant floor is developed and validated. Accurate temperature distribution of whole floor along the pipes can be obtained. A method to optimize design of radiant floor is proposed.